Aspek Hukum Pidana Dari Perbuatan Nahkoda - Priska Yulianti Wanda; Lidia Priscilla Pattiasina (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The legal issues in this writing is whether the act of transporting dangerous goods (B-3) that is not notified to the portmaster about the conditions of transportation can be qualified as a crime and whether the actions of the captain of transporting dangerous goods (B-3) are not appropriate. With the shipping requirements can be asked for criminal liability.Purposes of the Research:  This writing aims to find out and analyze the act of transporting dangerous goods (B-3 waste) that does not notify its capacity can be qualified as a crime, as well as discussing criminal responsibility for the actions of the captain who transports dangerous goods (B-3) that do not comply with shipping requirements.Methods of the Research: The research method used is normative, that is, research that primarily examines positive legal provisions and legal principles, explain and predicts in the direcrion of future legal developments.Results of the Research: The findings of this study prove that in the transportation of waste and special goods pays attention to the specifications of the ship. And the skipper as the carrier of dangerous goods (B-3) and special goods using transportation in waters without regard to specifications can be criminally accounted for from the criminal aspect on the basis of violating the provisions of Article 328 of Law no. 17 of 2008 in conjunction with Article 102 of Law no. 32 of 2009, because all the elements have been fulfilled, namely everyone who transports hazardous and toxic waste without paying attention to the specifications of the ship. The captain's actions violated Article 102 of Law no. 32 of 2009 and Article 328 of Law no. 17 of 2008, so that the captain can be sentenced to the heaviest criminal threat plus a third.